Wear and fracture of curettes due to sharpening and scaling processes. Issue 3 (9th January 2022) - Liu, Guojing; Liu, Xueling; Li, Na; Gao, Chengcheng; Cui, Ting; Luan, Qingxian; Wang, Jianmin
Abstract: Objectives: To examine the wear occurring in a group of new Gracey curettes due to the sharpening and scaling processes and record the number of service cycles before breakage. Methods: This study included 592 working ends of Gracey curettes that were subjected to cycles of sharpening and scaling. Three‐dimensional measurements of the blades and the status of the working ends were recorded before and after each process. Results: With an increase in the number of usage cycles, the three‐dimensional measurements of the blades decreased. During this study, 184 working ends were broken, of which 38.59% were of #11/12 Gracey curettes, and only 8.15% were of #7/8 Gracey curettes. The average number of cycles required for the fracture of Gracey curettes was 14.34. Cox regression analyses showed that the factors influencing the survival cycles were the tip width before usage and the type of Gracey curette. Moreover, the sharpening process was responsible for approximately half of the total instrument wear. Among the four types of Gracey curettes, the #11/12 Gracey curettes showed the greatest amount of sharpening wear, accounting for >50% of the total wear. Conclusions: The service life of Gracey curettes varies according to their types; the #11/12 Gracey curettes are more susceptible to breakage, while #7/8 Gracey curettes tend to have a long service life. Furthermore, the sharpening process was responsible for a considerable amount of curette wear.